INFLUENCE OF SMALL CHEMICAL ADDITIVES ON THE VELOCITY OF DETONATION WAVE AND THE DETONATION LIMIT IN RICH HYDROGEN MIXTURES (International Journal of Engineering Sciences & Management Research, 2014)
On the basis of Zel’dovich–von Neumann–Doering detonation theory with allowance for the theory of chain processes by theexample of the oxidation of hydrogen-rich mixtures in the presence of an inhibitor, it is shown that taking into account inhibitionreactions leads to the occurrence of “chemical” losses in addition to heat losses. “Chemical” losses alone can provide theoccurrence of concentration limit of detonation; the velocity of the combustion wave near the limit is supersonic. Theoreticalestimates agree qualitatively with the experimental data on the inhibition of a developing detonation wave in H2 –air mixtureswith additives of propane–butane mixture (0.5–4%) at 1 atm.